Le son dans les procès filmés en France - Martine Sin Blima-Barru (Criminocorpus)
During the trials of the terrorist attacks, between 2021 and 2024, two archivists from the National Archives of France went into the courtrooms to document the judicial action live, synchronising themselves with the complete recordings from the Justice Ministry’s audio-visual archives recorded during the 1,334 hours of filming. From this privileged placz, observation of the video recordings raises questions about the place that sound occupies in the creation of this archive. Faced with the material organisation used to reproduce it - fixed microphones, web radio – there is a more sensitive experience of the oral nature of the judicial debate. This very contemporary point of view invites us to go back in time to the first moving image recordings of trials, which were initially silent until their recording was banned in 1954. The return of the camera, wanted by Robert Badinter in 1985, is an archiving tool that also fixes the sound, restoring the materiality of filmed trials and inscribing them in our memory.